2017
DOI: 10.1097/ncm.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

The New Age of Bullying and Violence in Health Care: Part 3

Abstract: The increasing incidence and impact of bullying across all sectors have made it a major workforce performance management challenge. Health care settings are especially tense environments, often making it difficult for individuals to distinguish between bullying behavior and high expectations for staff. Bullying impacts both direct targets and bystanders who witness the assaultive behaviors, with ethical implications as well.Case management is poised to promote a safe health care workplace for patients and prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…10 Studies have shown turnover rates as high as 60% in healthcare workers on the receiving end of WPV. 11 The Workplace Bullying Institute also reports emotional impact on the victims by way of anxiety, panic attacks, depression and post-traumatic stress disorder. 12 In fact, cases of non-fatal injury and illness in relation to WPV are higher among healthcare workers than in any other industry.…”
mentioning
confidence: 99%
“…10 Studies have shown turnover rates as high as 60% in healthcare workers on the receiving end of WPV. 11 The Workplace Bullying Institute also reports emotional impact on the victims by way of anxiety, panic attacks, depression and post-traumatic stress disorder. 12 In fact, cases of non-fatal injury and illness in relation to WPV are higher among healthcare workers than in any other industry.…”
mentioning
confidence: 99%
“…Hutchinson, Jackson, Haigh, and Hayter (2013) noted that bullying tends to occur in environments of acquiescence, in the presence of others. Various behaviours are exhibited by bosses who bully others, to include physical aggression, blaming, ridiculing or putting leaders down in front of others, lying, accusing others of incompetence or not giving others credit for their work (Fink-Samnick, 2017;Moss, 2016). Some bullying bosses throw tirades and intimidate staff, while others are more covert and unpredictable and may be nice one day and abusive the next (Fink-Samnick, 2017).…”
Section: )mentioning
confidence: 99%
“…Various behaviours are exhibited by bosses who bully others, to include physical aggression, blaming, ridiculing or putting leaders down in front of others, lying, accusing others of incompetence or not giving others credit for their work (Fink-Samnick, 2017;Moss, 2016). Some bullying bosses throw tirades and intimidate staff, while others are more covert and unpredictable and may be nice one day and abusive the next (Fink-Samnick, 2017). Different theories exist for why leaders bully others (Hauge, Skogstad, & Einarsen, 2009).…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations